Modelos de resposta ao item com função de ligação t-assimétrica - Pinheiro, Alessandra Noeli Craveiro (2007)
The Item Response Theory (IRT) is a set of mathematical models representing the probability of an individual to take a correct response of an item and its ability. The purpose of our research is to show the models formulated in the IRT under the skew-normal distributions and to develop flexible alternative models. With this goal in mind we introduced the t-skew distributions (Azzalini et al. 1999) and results similar to Bazan s results are obtained. Some applications using Bayesian methods are also considered.